2003
DOI: 10.1074/jbc.m301348200
|View full text |Cite
|
Sign up to set email alerts
|

The 2.3-Å Crystal Structure of the Shikimate 5-Dehydrogenase Orthologue YdiB from Escherichia coli Suggests a Novel Catalytic Environment for an NAD-dependent Dehydrogenase

Abstract: We present here the 2.3-Å crystal structure of the Escherichia coli YdiB protein, an orthologue of shikimate 5-dehydrogenase. This enzyme catalyzes the reduction of 3-dehydroshikimate to shikimate as part of the shikimate pathway, which is absent in mammals but required for the de novo synthesis of aromatic amino acids, quinones, and folate in many other organisms. In this context, the shikimate pathway has been promoted as a target for the development of antimicrobial agents. The crystal structure of YdiB sho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
40
0

Year Published

2004
2004
2013
2013

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 47 publications
(44 citation statements)
references
References 49 publications
4
40
0
Order By: Relevance
“…A presumably bifunctional SDH has also been found in Escherichia coli (YdiB; EC 1.1.1.282). This enzyme also reduces quinate to 3-dehydroquinate with either NADP or NAD as a cosubstrate (Benach et al, 2003). NAD is mostly found in catabolic reactions.…”
Section: Introductionmentioning
confidence: 99%
“…A presumably bifunctional SDH has also been found in Escherichia coli (YdiB; EC 1.1.1.282). This enzyme also reduces quinate to 3-dehydroquinate with either NADP or NAD as a cosubstrate (Benach et al, 2003). NAD is mostly found in catabolic reactions.…”
Section: Introductionmentioning
confidence: 99%
“…This portion of the protein possesses a unique ␣-␤-␣ sandwich motif, which also includes an ␣-helical hairpin structure at the C terminus of the protein and is further referred to as domain 1. The intervening sequence, domain 2, forms a Rossmann fold, to which the dinucleotide cofactor is bound with the A side of the nicotinamide ring facing the interdomain cleft (12,21,23). A direct comparison of the cofactor complexes for the two E. coli enzymes AroE and YdiB by Michel et al (12) revealed structural differences in their nucleotide-binding motifs, which likely account for the 10-fold higher affinity of YdiB for NAD than for NADP.…”
mentioning
confidence: 99%
“…1 All of these structures reveal a common fold comprising two domains separated by a cleft. Although AroE from E. coli and AroE and YdiB from H. influenzae exist as monomers (12,22), YdiB from E. coli (12,23) and AroE from M. jannaschii (21) both homodimerize via their N-terminal domains. This portion of the protein possesses a unique ␣-␤-␣ sandwich motif, which also includes an ␣-helical hairpin structure at the C terminus of the protein and is further referred to as domain 1.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Expression and purification of Haemophilus influenzae hypothetical protein HI1161 and Xanthomonas campestris hypothetical protein XCC2852 (NESG targets IR63 and XcR50, 4 respectively) was carried out as part of the established high-throughput protein production pipeline of the NESG using previously published methods (Acton et al, 2005;Benach et al, 2003 ⎯ crystal structure of shikimate dehydrogenase).…”
Section: Protein Purification and Crystallizationmentioning
confidence: 99%